Combined effects of road salt and an insecticide on wetland communities. (28th October 2016) - Stoler, Aaron B.; Walker, Brent M.; Hintz, William D.; Jones, Devin K.; Lind, Lovisa; Mattes, Brian M.; Schuler, Matthew S.; Relyea, Rick A.
Abstract: As the numbers of chemical contaminants in freshwater ecosystems increase, it is important to understand whether contaminants interact in ecologically important ways. The present study investigated the independent and interactive effects of 2 contaminants that frequently co‐occur in freshwater environments among higher latitudes, including a commonly applied insecticide (carbaryl) and road salt (NaCl). The hypothesis was that the addition of either contaminant would result in a decline in zooplankton, an algal bloom, and the subsequent decline of both periphyton and periphyton consumers. Another hypothesis was that combining the contaminants would result in synergistic effects on community responses. Outdoor mesocosms were used with communities that included phytoplankton, periphyton, zooplankton, amphipods, clams, snails, and tadpoles. Communities were exposed to 4 environmentally relevant concentrations of salt (27 mg Cl – L −1, 77 mg Cl – L −1, 277 mg Cl – L −1, and 727 mg Cl – L −1 ) fully crossed with 4 carbaryl treatments (ethanol, 0 µg L −1, 5 µg L −1, and 50 µg L −1 ) over 57 d. Contaminants induced declines in rotifer and cladoceran zooplankton, but only carbaryl induced an algal bloom. Consumers exhibited both positive and negative responses to contaminants, which were likely the result of both indirect community interactions and direct toxicity. In contrast to the hypothesis, no synergistic effects were found, although copepod densities declined when high concentrations of both chemicals were combined. The results suggest that low concentrations of salt and carbaryl are likely to have mostly independent effects on aquatic communities. Environ Toxicol Chem 2017;36:771–779. © 2016 SETAC